The ProMotion LMU dataset (2022 edition), prostate intra-fraction motion recorded by transperineal ultrasound - Hendrik Ballhausen; Elena Kortmann; Claus Belka; Minglun Li (Scientific Data, 2022)
Measurement(s) intrafraction motion of the prostate Technology Type(s) transperineal ultrasound (4D) Sample Characteristic - Organism Homo sapiens Sample Characteristic - Environment hospital Sample Characteristic - Location Germany